Perlindungan Hukum Terhadap Notaris yang Melaporkan Pihak-Pihak dalam akta yang Terindikasi Tindak Pidana Pencucian Uang (TPPU) - Nadya Yusvira; Fitra Deni; Yoga Satrio (Jurnal Hukum Lex Generalis, 2025)
This research is a decision of application of the obligation for notary to report about money laundering, where If we examine and analyze the definition of a Notary as stated in Article 1 of Law Number 2 of 2014 concerning the Amendment to Law Number 30 of 2004 on the Position of Notary, the definition of a Notary is a Public Official who has the authority to create authentic deeds and other authorities based on further regulations. In carrying out their duties, a Notary, in accordance with their oath of office, has an obligation as stated in Article 16, paragraph 1 of Law Number 2 of 2014, which stipulates that a Notary, in performing their duties and position, must act with trust, honesty, caution, independence, impartiality, and protect the interests of the parties involved in the legal act. In interpreting Article 16, paragraph 1 of Law Number 2 of 2014, the clause "…protect the interests of the parties involved in the legal act" is often understood to mean that the Notary must guarantee the confidentiality of the interests of the prospective users of their services who are about to engage in a legal act. From the interpretation of Article 16, paragraph 1, many parties, including the author, interpret this as meaning that the notary must keep confidential the deed that will be made, as well as the identity of the prospective service users. There are also instances where some prospective users of notary services misuse or misinterpret the clause in Article 16, paragraph 1 to engage in unlawful acts. Some individuals believe that they are protected by the Notary Law and can easily commit illegal acts. One such illegal act is money laundering, where many service users take advantage of the notary to transfer assets used for committing money laundering offenses. Therefore, based on Article 17 of Law Number 8 of 2010, a notary is mandated to report any suspicious actions by their service users if the notary believes that the service user is involved in money laundering. However, this mandate in Law Number 8 of 2010 contradicts the provisions in Articles 4 and 16, paragraph 1 of the Notary Position Law, where a notary is required to maintain the confidentiality of the parties involved. However, when viewed in light of the lex specialis systematic principle, based on the public interest principle and the mandates of the 4th and 5th Pancasila, a notary must comply with the Anti-Money Laundering Law.